Pola Peresepan Obat Kemoterapi Kanker Payudara di Rumah Sakit Lavalette Kota Malang - Irawati Irawati; Mardhiyah Sardjan (PHARMADEMICA : Jurnal Kefarmasian dan Gizi, 2022)
Breast cancer is one type of malignant diseases with a high incidence both in Indonesia and in the world. It is the number one killer in Indonesia. Chemotherapy, as a method used in the breast cancer treatment, causes side effects that can interfere the quality of life of breast cancer patients. This study aims to determine the type of chemotherapy drugs, the combination of chemotherapy drugs in a prescription, and the dose of chemotherapy drugs at Lavalette Hospital. This study is descriptive research. It was conducted by collecting 100 sheets of breast cancer chemotherapy prescriptions in November 2020 as samples. Findings specify that the types of chemotherapy drugs for breast cancer that are often prescribed are cyclophosphamide 29%, docetaxel 19% and paclitaxel 17%. Combination of chemotherapy drugs that is often written down is the combination of 2 drugs of TdC (docetaxel cyclophosphamide) 36% and TpCar (paclitaxel, carboplatin) 33%. The dose writing for all types of drugs has been reviewed according to the patients’ weight, height and age.